How to write an experimental research paper - (:unkn) unknown (Springer Wien, 2002)
The art and practice of academic neurosurgery are mastered by defining and learning the pertinent basic principles and skills. This article aims to present general guidelines to one of the many roles of a neurosurgeon: Writing an experimental research paper. Every research report must use the "IMRAD formula: introduction, methods, results and discussion". After the IMRAD is finished, abstract should be written and the title should be "created". Your abstract should answer these questions: "Why did you start?, what did you do?, what answer did you get?, and what does it mean?". Title of the research paper should be short enough to catch glance and memory of the reader and be long enough to give the essential information of what the paper is about. Writing about the results of the experiment is no easier than the research itself. As surgery, writing a scientific paper is also an improvisation, but general principles should be learned and used in practice. The most effective style of learning basic skills to construct a research paper is the "trial and error" type.
Keywords: Abstract; Experiment; Neurosurgical education; Research